2003
DOI: 10.1242/dev.00711
|View full text |Cite
|
Sign up to set email alerts
|

Functional tests of enhancer conservation between distantly related species

Abstract: Expression patterns of orthologous genes are often conserved, even between distantly related organisms, suggesting that once established, developmental programs can be stably maintained over long periods of evolutionary time. Because many orthologous transcription factors are also functionally conserved, one possible model to account for homologous gene expression patterns, is conservation of specific binding sites within cis-regulatory elements of orthologous genes. If this model is correct, a cis-regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 62 publications
7
62
0
Order By: Relevance
“…By testing the expression pattern of enhancers from Drosophila in C. elegans, it has been shown that changes in cis-regulatory sequences accumulate relatively fast, while expression patterns remain conserved along animal evolution (Ruvinsky and Ruvkun 2003). This may explain why the motif pair was observed here only in the Caenorhabditis genus.…”
Section: Genome Research 79mentioning
confidence: 86%
“…By testing the expression pattern of enhancers from Drosophila in C. elegans, it has been shown that changes in cis-regulatory sequences accumulate relatively fast, while expression patterns remain conserved along animal evolution (Ruvinsky and Ruvkun 2003). This may explain why the motif pair was observed here only in the Caenorhabditis genus.…”
Section: Genome Research 79mentioning
confidence: 86%
“…Thus, the new regulatory architecture emerges beneath a constant phenotype, without any bottleneck in fitness during the transitional phase of mixed genotypes. Such neutral transitions may help explain apparent cases of ''developmental system drift,'' whereby closely related species achieved similar morphological structures by substantially different mechanisms (59,63,(71)(72)(73)(74).…”
Section: The Passive Emergence Of Modular Gene Interactionsmentioning
confidence: 99%
“…Although many of the key enzymes responsible for deposition and maintenance of H3K27me3 are known, it is likely that we do not have a complete catalog of all the elements of all PREs (Delest et al 2012), nor do we know the exact spatial or orientation requirements of the involved binding sites (if indeed there are any). However, the extreme conservation of H3K27me3 across distantly related species leads to the question of how a cis-regulatory element composed of relatively degenerate sequence motifs could persist functionally over such a long period of time (Ruvinsky and Ruvkun 2003;Fisher et al 2006).…”
Section: H3k27me3 Conservation Bypassed By Gene Duplicationmentioning
confidence: 99%